Managed Entry Agreements for Pharmaceuticals in the Context of Adaptive Pathways in Europe - Bouvy, Jacoline C.; Sapede, Claudine; Garner, Sarah (Frontiers in Pharmacology, 2018)
- As per the EMA definition, adaptive pathways is a scientific concept ftor the development of medicines which seeks to facilitate, through a patient access to promising medicines addressing high unmet need through a prospectively planned approach planned approach patient access to promising products addressing high unmet medical need in Europe in a sustainable way. - This review reports the findings of activities undertaken by the ADAPT-SMART consortium to identify enablers and explore the suitability of managed entry agreements for adaptive pathways products in Europe. - We found that during 2006-2016 outcomes-based managed entry agreements were not commonly used for products with a conditional marketing authorisation or authorised under exceptional circumstances. - The barriers and enablers to develop workable managed entry agreements models for adaptive